Will the Malaysian government make use of its good fortune? - Hamdan, Shahril (2023)
The recent by-election victories of the Pakatan Harapan-led ruling coalition underscore the fact that even when controversies abound, the government can count on a support base that appears to want to give it every chance to succeed. Now that it has momentarily arrested the opposition’s momentum, will it use these coming months to make bold reforms that matter?